A Review on the Cosmeceutical and External Applications of Nigella sativa - Ahmad M. Eid; Nagib A. Elmarzugi; Laila M. Abu Ayyash; Maher N. Sawafta; Hadeel I. Daana (Journal of Tropical Medicine)
It is estimated by the World Health Organization (WHO) that most of the world’s population depends on herbal medicine for their health care. Nigella sativa (N. sativa), also known as black-caraway and as “Kalonji,” is a well-known seed all over the world. It is one of the most common medicinal plants worldwide and contains many useful chemical constituents that we can find in its fixed oil, such as thymoquinone, thymohydroquinone, dithymoquinone, thymol, nigellicine, carvacrol, nigellimine, nigellicine, nigellidine, and alpha-hederin. Due to these numerous important ingredients it was found that it affects different areas of our body and has many pharmacological effects as antibacterial, antiviral, anti-inflammatory, and wound healing effect and also for acne vulgaris, skin cancer, pigmentation, and many cosmeceutical applications. Based on the folklore usage of N. sativa seeds and oil, they are used in various systems of food and medicines. The aim of this article is to provide a detailed survey of the literature of cosmeceutical and external applications of N. sativa which is expected to stimulate further studies on this subject.